2020
DOI: 10.3390/antiox9060524
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Necrostatin-1 in Parkinson’s Disease Models

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder that is characterized by the loss of dopaminergic neurons in the substantia nigra pars compacta. This neuronal loss, inherent to age, is related to exposure to environmental toxins and/or a genetic predisposition. PD-induced cell death has been studied thoroughly, but its characterization remains elusive. To date, several types of cell death, including apoptosis, autophagy-induced cell death, and necrosis, have been implicated in PD progression. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Here, we reported for INS-1 β-cells a high toxicity of rotenone after 24 h with an IC 50 = 30 nM, which is very similar to that found for dopaminergic-like cell lines. Intriguingly, in other cell types, such as microglial cells, breast cancer cells and fibroblasts, rotenone was toxic but at higher concentrations, showing a similarity between β-cells and dopaminergic cell lines in terms of high vulnerability to rotenone [42][43][44]. Regarding the mechanism of action, rotenone acts as mitochondrial complex I inhibitor and it has been used as a PD model for both in vitro and in vivo studies [25] (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we reported for INS-1 β-cells a high toxicity of rotenone after 24 h with an IC 50 = 30 nM, which is very similar to that found for dopaminergic-like cell lines. Intriguingly, in other cell types, such as microglial cells, breast cancer cells and fibroblasts, rotenone was toxic but at higher concentrations, showing a similarity between β-cells and dopaminergic cell lines in terms of high vulnerability to rotenone [42][43][44]. Regarding the mechanism of action, rotenone acts as mitochondrial complex I inhibitor and it has been used as a PD model for both in vitro and in vivo studies [25] (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from retinal degeneration, the protective effect of Nec-1 has been observed in other neurological disease models as well (like PD [ 176 ] and axonal degeneration [ 177 ]). It is also reported that Nec-1 could ameliorate neural cell injury induced by aluminum, a common metal material which can be transported to the brain and contribute to AD etiology [ 178 ].…”
Section: Role Of Nec-1 In Disease Modelsmentioning
confidence: 99%
“…However, in mouse microglia cells (BV-2 or N9 cell lines, primary microglia) exposed to z-VAD-fmk and/or LPS and/or BV6 (SMAC mimetic), Nec-1 abolished cell damage induced by these factors, and this effect was associated with the inhibition of necroptotic factors (RIP1/RIP3/MLKL) and reduction in pJNK/JNK level [111]. Although Nec-1 was demonstrated to inhibit necroptosis induced by rotenone in SH-SY5Y cells measured by decreased level of pMLKL, it did not reduce but even exaggerated the Rot-evoked cell damage [112]. Additionally, in another neuronal cell type, namely RGC-5 cells, Nec-1 did not attenuate rotenone toxicity, whereas inhibitors of JNK and p38 pathways exerted beneficial effects in this model [113].…”
Section: Neuroprotective Effects Of Necroptosis Inhibitors In In Vitro Models Of Parkinson's Diseasementioning
confidence: 97%